14th of the International Conference on Hydroscience and Engineering, Iche 2022: Proceeding Book - Elçi, Şebnem; Elçi, Şebnem; Bombar, Gökçen (Izmir Institute of Technology, 2022)
14th of the International Conference on Hydroscience & Engineering, ICHE 2022 will be held in Izmir, Turkey on 26-27 May, 2022. The International Conference on Hydroscience & Engineering began in Washington DC in 1993, and followed by Beijing hosted ICHE in 1995, Cottbus (1998), Seoul (2000), Warsaw (2002), Brisbane (2004), Philadelphia (2006), Nagoya (2008), Chennai (2010), Orlando (2012), Hamburg (2014) Tainan (2016) and Chongqing (2018). These conferences provided a common ground researchers and engineers to report and discuss the latest scientific advancements and practitioner’s solutions in hydroscience and engineering. ICHE 2022 conference aims to bring together researchers and practicing engineers to share the latest scientific and technological advancements in hydroscience and engineering, and will provide networking opportunities for future activities. Participants will be able to hear experts in the field discuss the latest achievements in issues relevant to Hydro-Engineering for Sustainable Development.
Iche 2022: Proceeding Book
Proceedings of 14th of the International Conference on Hydroscience & Engineering, ICHE 2022; 26-27 May, 2022 İzmir-Türkiye
Keywords: Hydroscience; Water resources; Water quality; Sediment transport; Urban flooding